Beyond love is love: investigating LGBTQIA+ parent-influencers’ advocacy work on Instagram - Bussoletti, Arianna (AoIR Selected Papers of Internet Research, 2026)
The paper focuses on Instagram LGBTQIA+ parent-influencers in the Italian context, where traditional gender stereotypes are still predominant and LGBTQIA+ individuals’ rights are well-below EU standards (ILGA-Europe 2024). Through thematic analysis of a three-month digital ethnography of the two largest profiles of Italian LGBTQIA+ parent-influencers, the contribution highlights both: 1) LGBTQIA+ parent-influencers’ use of digital platforms to negotiate identity-based stigma, providing alternative models of gender, sexuality, and family; and 2) the political potential of this form of advocacy-work. Preliminary findings highlight how the profiles contend with integration and social advocacy. On the one hand, they seek to dismantle stereotypes that see queer parenthood as ‘other’ and selfish through relatable portrayals of family life; on the other, they engage with questions of politics and activism, often due to a perceived duty to educate audiences. These practices highlight the profiles’ efforts to familiarize audiences with the challenges faced by LGBTQIA+ families and overcome the ‘love is love’ trope of social inclusion, which often has the result of depoliticizing queer struggles. Given a relative lack of symbolic LGBTQIA+ figures and events in Italy, LGBTQIA+ parent-influencers can allow scholars a glimpse into the cultural and social presence of these subjectivities. Their tug-o-war between relatable-ness and activism underscores questions regarding the potential for social change of this kind of content and how it is reconciled with the logics of platform capitalism.